An ergonomic assessment among administrative workers in higher learning institution - Mohamad Syazwan Hanif, Abd Latif (2019)
Work-related musculoskeletal disorder (WRMSD) are one of the most occupational among administrative workers. It was often causes many physical and physiological factors of administrative workers. In addition, WRMSD were causes of financial burden for health-care system and performance of worker. Hence, the aim of this study was conduct to determine the prevalence of work related musculoskeletal disorder. Moreover, this study was to identify physical factor, analyze ergonomic risk factor and also determine the association between prevalence of WRMSD complaint and ergonomic risk factors. In this study, 135 respondents from many departments in Universiti Malaysia Pahang (UMP) had been involved. The study was carried out among administrative workers. Data collection was done using two instruments, namely Self-Assessment Musculoskeletal Pain/Discomfort Survey Form and Initial Ergonomic Risk Assessment (ERA). Self-Assessment Musculoskeletal Pain/Discomfort Survey Form was used to collect data on the prevalence of WRMSD complaints. Meanwhile, Initial Ergonomic Risk Assessment (ERA) to measure and determine ergonomic risk factors among administrative workers. The results showed the lower back was the most identified prevalence of WRMSD among the respondents. Moreover, awkward posture is the highest ergonomic risk factor on percentage of Initial ERA score. In addition, it was agreeing that prevalence of WRMSD was influenced the ergonomic risk factors. The result also found that there was an association between the two variable which was prevalence of WRMSD and ergonomic risk factors when comparing Self-Assessment and Initial ERA.